Especifica??o de uma plataforma referencial convergente para a nova gera??o de redes sem fio - Pereira, Get?lio Em?lio Oliveira (2013)
Hundreds of initiatives to redefine the Internet are being undertaken to meet the needs of our information society in the coming decades. These efforts are collectively called the Future Internet. Meanwhile, the research on digital wireless communication systems proceeds in the direction of increasing the radio spectrum utilization efficiency, as well as in creating platforms that facilitate migration to new technologies and protocols. The new data communication terminals must be able to learn about the environment in which they are using the available communication channels and avoiding interference with licensed users. These radio terminals are called cognitive radios. In this work, technologies from both fronts are integrated in order to create a reference model for the cognitive radio terminals of the Future Internet.